2021
DOI: 10.9744/jmk.23.2.186-196
|View full text |Cite
|
Sign up to set email alerts
|

#I Envy, Therefore, I Buy! #: The Role of Celebgram Trustworthiness and Para-Social Interactions in Consumer Purchase Intention

Abstract: Businessmen’s marketing strategies that take advantage of the fame of celebgrams as influencers are incredibly appropriate in the social media era. The present study deals with the dynamics of celebgram trustworthiness and social interaction with their followers in relation to possession envy and consumer purchase intention. To test the proposed model, the researchers collected data from 181 respondents in Indonesia through an online survey and analyzed it using the Smart PLS. The results of the present study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Previous research reveals that social influence in the particular referenced group influences someone's attitude and behavior directly and indirectly (Najib et al, 2022). The influence of social role models such as trust in celebgram and social interaction on ownership jealousy needs to be considered in the influencer marketing on social media to increase consumers' buying interest (Purwanto, 2021). Respondents focus their attention on images rather than text on Instagram.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research reveals that social influence in the particular referenced group influences someone's attitude and behavior directly and indirectly (Najib et al, 2022). The influence of social role models such as trust in celebgram and social interaction on ownership jealousy needs to be considered in the influencer marketing on social media to increase consumers' buying interest (Purwanto, 2021). Respondents focus their attention on images rather than text on Instagram.…”
Section: Resultsmentioning
confidence: 99%
“…Respondents focus their attention on images rather than text on Instagram. Compared to Facebook, the text is more concerned, so the influence of social influence may be limited (Purwanto, 2021). According to Sambe and Haryanto (2021), consumers believe that buying a virtual item can help them to find new friends and build or even maintain a social relationships between consumers.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Kurtin [ 37 ] investigated the factors of para-social relationships on YouTube and found that three types of attractiveness and exposure have an effect on para-social relationships. Purwanto [ 38 ] analyzed the effect of para-social relationships on celebrities. The study showed that para-social interactions on social media have an impact on purchase intention.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Para-social relationships with attractive characters have been found to be important in media use [ 30 , 38 ]. Online celebrities are influential, as viewers can easily have relationships with them by posting comments or through donations [ 23 ].…”
Section: Quantitative Design and Data Analysis (Phase 2)mentioning
confidence: 99%
“…Simultaneously, envy can also have a positive implication that motivates people to improve their position by stimulating consumption (van de Ven, 2016; Lins et al, 2015). Various studies have indicated that envy plays an important role in determining consumers' buying behaviour (Lin & Utz, 2015; Purwanto, 2021). Munawar et al (2021) indicated that envious people are more involved in buying products that satisfy their hedonic shopping motives.…”
Section: Hypotheses Development and The Conceptual Modelmentioning
confidence: 99%